2017
DOI: 10.1002/ajmg.a.38086
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional bone impairment in Noonan syndrome

Abstract: Noonan syndrome (NS) is an autosomal dominant trait characterized by genotypic and phenotypic variability. It belongs to the Ras/MAPK pathway disorders collectively named Rasopathies or neurocardiofaciocutaneous syndromes. Phenotype is characterized by short stature, congenital heart defects, facial dysmorphisms, skeletal and ectodermal anomalies, cryptorchidism, mild to moderate developmental delay/learning disability, and tumor predisposition. Short stature and skeletal dysmorphisms are almost constant and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Increased bone resorption has previously been reported in RASopathies (D. Stevenson et al, 2011; D. A. Stevenson et al, 2008). Specifically, reduced BMD has been documented in NF1 (Heervä et al, 2012; D. A. Stevenson et al, 2007) and anecdotally in NS and CS (Baldassarre et al, 2017; Leoni et al, 2014; White et al, 2005). In NF1 mouse models, a reduced mineral content associated with decreased bone stiffness has been found (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased bone resorption has previously been reported in RASopathies (D. Stevenson et al, 2011; D. A. Stevenson et al, 2008). Specifically, reduced BMD has been documented in NF1 (Heervä et al, 2012; D. A. Stevenson et al, 2007) and anecdotally in NS and CS (Baldassarre et al, 2017; Leoni et al, 2014; White et al, 2005). In NF1 mouse models, a reduced mineral content associated with decreased bone stiffness has been found (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Choudry et al reported a statistically significant reduction in BMD z‐scores and a trend toward significance for BMC z ‐scores in children with NS compared to age‐matched controls (Choudhry et al, 2012). In the same way, Baldassarre et al investigated bone quality via quantitative ultrasound and metabolic bone profiling in a group of 35 patients with NS demonstrating bone impairment in NS (Baldassarre et al, 2017). In CS anecdotal data have been reported dealing with osteopenia or osteoporosis, mostly for adult patients (D. Stevenson et al, 2011; D. A. Stevenson & Yang, 2011; White et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ptpn11 mutations lead to increased SHP2 enzymatic activity and altered activation of the Ras/RAF/ERK signaling cascade responsible for Noonan syndrome (NS). NS is an autosomal dominant disorder characterized by dysmorphic facial features, proportionate short stature, and decreased bone mineral density (BMD), 80 , 81 as well as heart disease. 82 , 83 To circumvent the lethality of SHP2 null mutations and study SHP2’s function in the osteoblastic cell lineage, Ptpn11 floxed alleles have been created 13 , 77 and bred with a series of Cre alleles to target osteoblastic cells at various developmental stages.…”
Section: Ptps In Osteoblast Development Function and Bone Homeostasismentioning
confidence: 99%
“…Reduced bone mineral density (BMD) has been documented in both NF1patients and animal models (Elefteriou et al, 2006; Illés et al, 2001; Kuorilehto et al, 2005; Stevenson, Murray, et al, 2008; Wu et al, 2006; Yang et al, 2006; Yilmaz et al, 2007; Yu et al, 2005). Bone assessment has recently been analyzed also in NS and CS (Baldassarre et al, 2017; Choudhry et al, 2012; Leoni et al, 2014; Leoni et al, 2021), whereas a systematic assessment of BMD and bone mineral homeostasis in CFCS is lacking. Of note we recently documented a low BMD occurring in patients with CS, which was associated with a marked reduction of blood 25‐hydroxyvitamin D (25(OH)vitD), suggesting a possible strategy based on supplementation of this vitamin for managing this complication in CS (Leoni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%